Activity measurement of Ga in liquid Ga-Pb alloys by EMF method with zirconia solid electrolyte - Katayama I.; Živković Dragana; Manasijević Dragan; Oishi T.; Živković Živan D.; Iida T. (Journal of Mining and Metallurgy. Section B: Metallurgy)
EMF measurement of the electrochemical cell with zirconia as solid electrolyte was performed to determine the gallium activity from 950 to 1150K in the entire composition range of liquid Ga-Pb alloys. In the whole concentration range, activity of Ga shows moderately positive deviations from ideality, and activity of Pb which is derived by Gibbs- Duhem equation shows also positive deviation from ideality. These are compared with published data obtained by different experimental methods.